Profitability, Liquidity and Earning Per Share Against Share Prices in Food and Beverage Companies: Profitabilitas, Likuiditas dan Earning Per Share Terhadap Harga Saham pada Perusahaan Makanan dan Minuman - Sakdiyah, Aminatus; Hariasih, Misti (Indonesian Journal of Innovation Studies, 2023)
The purpose of this study is to prove the effect of profitability, liquidity, and earnings per share on stock prices. This study uses quantitative methods and uses secondary data. The data used in this study is secondary time data from Profitability, Liquidity and Earning Per Share and Stock Prices for the 2016-2020 period. Sampling of this research using purposive sampling method. Annual data for each variable for 5 years and 10 food and beverage companies listed on the IDX. This study uses multiple linear analysis techniques with the application of eviews 9. The results of this study indicate that partially the profitability variable has a negative and significant influence on stock prices, the Liquidity variable has a positive and significant influence on stock prices, and the Earning Per Share variable has a positive influence. significant to stock prices. And simultaneously Profitability, Liquidity, and Earning Per Share affect the stock price of food and beverage companies listed on the IDX.